2019
DOI: 10.3389/fbioe.2019.00010
|View full text |Cite
|
Sign up to set email alerts
|

Soil Bacterial Communities From the Chilean Andean Highlands: Taxonomic Composition and Culturability

Abstract: The Atacama Desert is a highly complex, extreme ecosystem which harbors microorganisms remarkable for their biotechnological potential. Here, a soil bacterial prospection was carried out in the high Altiplano region of the Atacama Desert (>3,800 m above sea level; m a.s.l.), where direct anthropogenic interference is minimal. We studied: (1) soil bacterial community composition using high-throughput sequencing of the 16S rRNA gene and (2) bacterial culturability, by using a soil extract medium (SEM) under a fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 76 publications
2
28
0
Order By: Relevance
“…For instance, members of Actinobacteria and Firmicutes, Gram-positive bacterial phyla widely found in drylands (7,13,14,16), are well known for their ability to form highly stress-resistant spores (17,18). Consistently, these sporulating taxa are among the most common groups identified in desert soils (19)(20)(21)(22) based on both conventional cultivation studies and modern molecular phylogenetic analyses. Common Cyanobacteria isolated from desert biocrusts, such as Anabaena, Nostoc, and Cylindrospermum (23,24), can differentiate into specific spore-like structures termed akinetes, which tend to be much larger in size than their vegetative structures (25).…”
mentioning
confidence: 97%
“…For instance, members of Actinobacteria and Firmicutes, Gram-positive bacterial phyla widely found in drylands (7,13,14,16), are well known for their ability to form highly stress-resistant spores (17,18). Consistently, these sporulating taxa are among the most common groups identified in desert soils (19)(20)(21)(22) based on both conventional cultivation studies and modern molecular phylogenetic analyses. Common Cyanobacteria isolated from desert biocrusts, such as Anabaena, Nostoc, and Cylindrospermum (23,24), can differentiate into specific spore-like structures termed akinetes, which tend to be much larger in size than their vegetative structures (25).…”
mentioning
confidence: 97%
“…), available phosphorus (P Olsen ) or pH. Atacama Desert soils are characterized by their high salinity where commonly are isolated salt tolerance culturable bacteria (4-8% NaCl) (Okoro et al, 2009;Maza et al, 2019). Factors influencing the rapid variation and adaptation of rhizobacterial communities are identified as plant genotype, phenological stages of plants, composition of rhizodeposits, bacterial assemblages, microenvironment generated by a whole set of plants or bacterial interactions (Fernández-Gómez et al, 2019), especially considering that some bacterial taxa observed in this study are also influenced in their distribution and diversity in short periods of time by diurnal cycling (Staley et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Acidobacteria may participate in the biodegradation process of cultural relics. Nitrifying bacteria and acidophilic bacteria were also found in the soil of the Jinsha earthen relic, and might contribute to surface degradation of soil through the conversion of ammonia in the extracellular matrix into nitrite and nitric acid [ 50 ], or the secretion of organic acids (under abnormal conditions, microorganisms may secrete citric acid and pyruvate) [ 51 , 52 ]. Additionally, Bacillus and Pseudomonas bacteria were also identified in the Jinsha earthen site samples.…”
Section: Discussionmentioning
confidence: 99%
“…conditions, microorganisms may secrete citric acid and pyruvate) [51,52]. Additionally, Bacillus and Pseudomonas bacteria were also identified in the Jinsha earthen site samples.…”
Section: Plos Onementioning
confidence: 94%